Computational intelligence in music, sound, art and design : 8th International Conference, EvoMUSART 2019, held as part of EvoStar 2019, Leipzig, Germany, April 24-26, 2019, Proceedings /: 8th International Conference, EvoMUSART 2019, held as part of EvoStar 2019, Leipzig, Germany, April 24-26, 2019, Proceedings. (2019) - Unknown
No abstract available